If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3K + 2(3) = K Multiply 2 * 3 3K + 6 = K Reorder the terms: 6 + 3K = K Solving 6 + 3K = K Solving for variable 'K'. Move all terms containing K to the left, all other terms to the right. Add '-1K' to each side of the equation. 6 + 3K + -1K = K + -1K Combine like terms: 3K + -1K = 2K 6 + 2K = K + -1K Combine like terms: K + -1K = 0 6 + 2K = 0 Add '-6' to each side of the equation. 6 + -6 + 2K = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 2K = 0 + -6 2K = 0 + -6 Combine like terms: 0 + -6 = -6 2K = -6 Divide each side by '2'. K = -3 Simplifying K = -3
| 115=2.5x+35 | | n+n=-2 | | 2n+2=-50 | | 6(2x-9)=28 | | N*3=36 | | 48=n | | x+x+8=332 | | N+32=45 | | .02(x+3)-4(2x-3)=3.4 | | 3k+6=k | | (9x^2-18x+5)= | | -4x+-3y=30 | | -5=-19 | | 2y+4=38 | | g=2+6t | | n^6=6 | | 5-2y=1.5 | | 9x-6=3x-30 | | 7a+4=5a+8 | | 7(b-5)+12=5 | | 16Y=15(y+13) | | 4f-2=18 | | -107=3+10x | | 0.04(12)+0.01x=0.02(12+x) | | 2x-18=5x+12 | | -7(3x+9)=-21x+63 | | n+21=24 | | 4x+b=3x+7 | | 5(5x-20)=25(x-20) | | 8y-8=37-7t | | 9x^2-18x+5= | | y-6=x |